Bulk Explosives Testing at the Red Dog Mine in Northwestern Alaska - John Kells; Norman Paley (International Society of Explosives Engineers, 2004)
The climate and location of the Red Dog Mine present several challenges to blasting operations. The mine is located north of 68º latitude, in an area of continuous permafrost. Ground temperatures are below freezing year-round and air temperatures range from -40 to 70°F (-40 to 20°C). Because there is no overland access to the mine, the entire year’s supply of bulk explosives, approximately 7,000,000lbs (3,175,000kg) is shipped in by barge during the 100 day shipping season when the port is ice-free. The first week in July is the earliest that new product arrives at the port. Emulsion usage is maximized from mid April through October when surface water fills the blastholes during drilling. This necessitates that a considerable portion of the bulk explosives are stored for 10 months or more before usage. The emulsion is routinely pumped from the ISO containers at temperatures of 20ºF (-7°C). The mine engineers conducted a testing program during the 2001-2 blasting season to identify the bulk explosives best suited for the conditions at the mine. A secondary goal was to decrease the usage of sensitized emulsion, as this is the most difficult portion of the explosives order to ship. To ensure repeatability when transferring the results to the day-to-day blasting operation, the majority of the testing was incorporated into normal blasting operations in the field. The mining methods used at Red Dog Mine make direct fragmentation analysis impractical and performance testing in the field relied primarily on VOD measurements. The products were also tested for their ability to be pumped in cold temperatures.